2005
DOI: 10.1200/jco.2005.07.116
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Among Localized Prostate Cancer Survivors: Health-Related Quality-of-Life Changes After Radical Prostatectomy, External Radiation, and Brachytherapy

Abstract: During a 4-year interval from earlier to longer-term phases of PC treatment survivorship, sexual, urinary, and bowel dysfunction remain significant concerns among early-stage PC treatment survivors, compared with control men. Although postprostatectomy HRQOL remains relatively stable during this interval, disease-specific HRQOL continues to evolve among men treated with BT and 3-D CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
234
6
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(257 citation statements)
references
References 42 publications
13
234
6
2
Order By: Relevance
“…Our findings extend the potential applications of a CArG inducible TNFbased gene therapy to patients' tumors where cytotoxins or radiation are either ineffective or poorly tolerated. For example, in prostate cancer, where radiotherapy and surgery are strongly associated with impotence, incontinence and rectal injury, 22 cytotoxic therapy via local infection with TNFerade and induction by resveratrol might offer an attractive alternative. More broadly, combining resveratrol with stable transduction of target tissues by CArG-dependent expression vectors might provide a practical answer to a current challenge for gene therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings extend the potential applications of a CArG inducible TNFbased gene therapy to patients' tumors where cytotoxins or radiation are either ineffective or poorly tolerated. For example, in prostate cancer, where radiotherapy and surgery are strongly associated with impotence, incontinence and rectal injury, 22 cytotoxic therapy via local infection with TNFerade and induction by resveratrol might offer an attractive alternative. More broadly, combining resveratrol with stable transduction of target tissues by CArG-dependent expression vectors might provide a practical answer to a current challenge for gene therapy.…”
Section: Resultsmentioning
confidence: 99%
“…[6,11] The urinary irritative symptoms most commonly reported by patients after brachytherapy or radiotherapy include dysuria and frequency. [10] Changes in long-term urinary outcomes more than 1 year after brachytherapy are not well characterized as of yet, because sample size for later follow-up in these studies was low due to loss of follow-up. It should be noted that dysuria is not measured by the AUA-SI instrument, which has been used by some investigators to evaluate post-brachytherapy changes in urinary HRQOL.…”
Section: Impact Of Primary Prostate Cancer Treatment On Specific Hrqomentioning
confidence: 99%
“…The bowel/rectal problems are not as prevalent as is sexual dysfunction after prostate cancer treatment, but appear to have an overall impact (in terms of severity of bother) closer to that of the urinary HRQOL domain. [8,10] The onset of these symptoms occurs during or early after treatment, and can linger into later follow-up. A multivariable analysis of the HMS cohort suggested that bowel and rectal symptoms were less profound after brachytherapy than after external beam radiotherapy.…”
Section: Impact Of Primary Prostate Cancer Treatment On Specific Hrqomentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Radiation therapy is associated with similar QOL deficits, including sexual dysfunction, exacerbation of obstructive urinary symptoms, and bothersome bowel symptoms. [3][4][5] As a result, there has been long-standing interest in assessing quality-of-life outcomes among this patient population. However, prior efforts in this area have been primarily research oriented, focusing on instrument development, measurement and assessment of treatment-related consequences.…”
Section: Introductionmentioning
confidence: 99%